Modeling of anisotropic dual scale flow in RTM using the finite elements method - Facciotto, Silvio; Simacek, Pavel; Advani, Suresh G.; Middendorf, Peter (Composites. Part B, Engineering, 2021)
In Liquid Composite Molding (LCM) processes, a fabric reinforcement is placed in a closed cavity and resin is injected into the mold. Almost all reinforcements are dual scale containing fiber tows, which fill at a different rate than the region in between the fiber tows. Simulation of LCM processes can help identify regions that fail to fill. However, the presence of dual scale flow is usually neglected. Here this phenomenon is modeled using Liquid Injection Molding Simulation (LIMS) software in which a complex network of one-dimensional elements is created. This allowed us to simulate transverse and longitudinal flow through the fiber tows taking into consideration the orientation and architecture of the reinforcement and, additionally, adding capillary effects to the model. A sensitivity study has been performed to investigate the effects of properties in non-dimensional form, allowing for comparison with experiments that were conducted to validate the model by visualization of the flow front position and dual scale area dimensions. [Display omitted] •Dual scale flow simulation through complex one-dimensional elements network.•Simulation of anisotropic flow inside fiber tows with low computational effort.•Validation through experiments visualizing flow front and dual scale area.•Parametric study with non-dimensional properties showing model capability.•Study of tow compaction variability using experimental data.